Can the calf-raise senior test predict functional fitness in elderly people? A validation study using electromyography, kinematics and strength tests. (July 2018) - André, Helô-Isa; Carnide, Filomena; Moço, Andreia; Valamatos, Maria-João; Ramalho, Fátima; Santos-Rocha, Rita; Veloso, António
Abstract: The assessment of the plantar-flexors muscle strength in older adults (OA) is of the utmost importance since they are strongly associated with the performance of fundamental tasks of daily life. The objective was to strengthen the validity of the Calf-Raise-Senior (CRS) test by assessing the biomechanical movement pattern of calf muscles in OA with different levels of functional fitness (FF) and physical activity (PA). Twenty-six OA were assessed with CRS, a FF battery, accelerometry, strength tests, kinematics and electromyography (EMG). OA with the best and worst CRS scores were compared. The association between the scores and EMG pattern of ankle muscles was determined. OA with the best CRS scores presented higher levels of FF, PA, strength, power, speed and range of movement, and a more efficient movement pattern during the test. Subjects who scored more at the CRS test demonstrated the possibility to use a stretch-shortening cycle type of action in the PF muscles to increase power during the movements. OA with different levels of FF can be stratified by the muscular activation pattern of the calf muscles and the scores in CRS test. This study reinforced the validity of CRS for evaluating ankle strength and power in OA. Highlights: The assessment of ankle muscle strength is important due to its close link with the elderly's activities of daily living. This study reinforced the validity of the Calf-Raise-Senior test for evaluating ankle strength and power in older adults. This test is simple to perform, doesn't require much equipment and allows easy access to information on elderly functionality.